2005
DOI: 10.1007/s10549-004-6019-9
|View full text |Cite
|
Sign up to set email alerts
|

Soyfood intake and breast cancer survival: a followup of the Shanghai Breast Cancer Study

Abstract: Soy and its constituents have been shown in many in vivo and in vitro studies and in some epidemiological studies to have anti-cancer effects. Some soy constituents, however, also stimulate cell proliferation, which has raised concerns in promoting soy intake among breast cancer survivors. To investigate whether soy intake may be associated with breast cancer survival, we evaluated data from a cohort of 1459 breast cancer patients who participated in the Shanghai Breast Cancer Study between 1996 and 1998. Usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 17 publications
4
76
1
Order By: Relevance
“…Among Chinese women in Shanghai, usual soy food intake before breast cancer diagnosis was unrelated to disease-free breast cancer survival after a median follow-up of 5.2 years, but information on tamoxifen use was not included (Boyapati et al, 2005). To address the concern that soy may negate the effect of tamoxifen (Messina et al, 2006), we investigated and found no relationship between serum levels of tamoxifen or its metabolites and self-reported intake of soy or serum levels of isoflavones among a population-based sample of Asian-American women with breast cancer (Wu et al, 2007b).…”
Section: Soy and Breast Cancer Survivalmentioning
confidence: 99%
“…Among Chinese women in Shanghai, usual soy food intake before breast cancer diagnosis was unrelated to disease-free breast cancer survival after a median follow-up of 5.2 years, but information on tamoxifen use was not included (Boyapati et al, 2005). To address the concern that soy may negate the effect of tamoxifen (Messina et al, 2006), we investigated and found no relationship between serum levels of tamoxifen or its metabolites and self-reported intake of soy or serum levels of isoflavones among a population-based sample of Asian-American women with breast cancer (Wu et al, 2007b).…”
Section: Soy and Breast Cancer Survivalmentioning
confidence: 99%
“…Further research is therefore needed to determine effect of soy foods or isoflavones on breast cancer risk in high-risk women and on the survival of breast cancer patients [40]. Although, a Chinese study found no relationship between soy food intake before diagnosis and survival [41], it is not recommended to use soy to reduce menopausal symptoms in breast cancer patients [4].…”
Section: Phytoestrogenesmentioning
confidence: 99%
“…Regarding to the associations between soy food intake after cancer diagnosis and survival (mortality or recurrence), the results were not the same based on available cohort studies (Guha et al, 2009;Shu et al, 2009;Kang et al, 2010;Caan et al, 2011;Nechuta et al, 2012;Zhang et al, 2012). One meta-analysis of four prospective cohort studies (Boyapati et al, 2005;Fink et al, 2007;Guha et al, 2009;Shu et al, 2009) showed that soy isoflavones intake was inversely associated with risk of breast cancer recurrence (Dong et al, 2011). However, two (Boyapati et al, 2005;Fink et al, 2007) of them investigated whether soy intake prior to cancer diagnosis might be associated with breast cancer survival, and the rest (Guha et al, 2009;Shu et al, 2009) evaluated whether soy intake after cancer diagnosis might be associated with breast cancer survival.…”
Section: Introductionmentioning
confidence: 97%
“…As Feng Chi*, Rong Wu, Yue-Can Zeng, Rui Xing, Yang Liu, Zhao-Guo Xu a result, clinicians treating women with breast cancer frequently caution them to either avoid soy foods entirely or use them in moderation (Doyle et al, 2006;Helferich et al, 2008;Velentzis et al, 2008). A cohort study of 1459 Chinese breast cancer patients who commonly eat soy foods prior to cancer diagnosis showed that there were not any association between soy food intake and disease-free breast cancer survival (Boyapati et al, 2005). And another study conducted by Fink et al (Fink et al, 2007) reported that reduced hazard ratios [hazard ratio (95% confidence interval)] for all-cause mortality were observed among premenopausal and postmenopausal women for the highest quintile of intake prior to cancer diagnosis, compared with the lowest, for isoflavones [0.52 (0.33-0.82)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation